Descripción del bienestar psicológico en adultos jóvenes y el vínculo humano-canino (2021)
The present quantitative study in which psychological well-being was evaluated as an index in itself and not a predictor, emphasizing: self-acceptance, positive relationships, autonomy, mastery of the environment, personal growth and life purpose and the human bondcanine regarding: Dog-Owner interaction, perception of emotional closeness and perceived costs. The Ryff Psychological Well-being scale and the Monash scale were used to assess the humancanine bond. A sample of 50 young adults was taken, selected for convenience, with a nonexperimental, cross-sectional design. The results showed that psychological well-being is 94% accumulated with a high level, it is and the canine Human bond with 82% accumulated above the average; indicating that the bond favors personal behaviors in social and emotional.